Political Ethics in the Thought of Abu Hamid al-Ghazali - Muhammad Azrul Amirullah; Fazari Zul Hasmi Kanggas; Saipul Nasution (ASANKA : Journal of Social Science and Education, 2026)
This study examines the concept of political ethics in the thought of Abu Hamid al-Ghazali and its relevance to contemporary governance discourse. The research is motivated by the increasing crisis of political morality, corruption, abuse of power, and the separation between ethics and politics in modern political systems. Using a qualitative library research method with a normative-philosophical approach, this study analyzes Al-Ghazali’s major works concerning leadership, justice, authority, and the relationship between religion and state. The findings demonstrate that Al-Ghazali viewed politics as an ethical instrument aimed at realizing public welfare (maṣlaḥah), justice, social harmony, and political stability. According to Al-Ghazali, religion serves as the moral foundation of society, while political authority serves as its guardian, maintaining order and preventing social chaos. Ethical leadership, therefore, must be grounded in justice, responsibility, spirituality, and public accountability. This study also finds that Al-Ghazali’s political ethics remain relevant in addressing contemporary governance challenges, particularly in promoting moral integrity and social justice. This study offers a normative model of political ethics integrating moral-spiritual values with governance principles. Consequently, Al-Ghazali’s thought provides an important ethical framework for developing a more humane, just, and morally responsible political order in the modern era.